2017
DOI: 10.1007/s00253-017-8666-x
|View full text |Cite
|
Sign up to set email alerts
|

Starter cultures as biocontrol strategy to prevent Brettanomyces bruxellensis proliferation in wine

Abstract: Brettanomyces bruxellensis is a common and significant wine spoilage microorganism. B. bruxellensis strains generally detain the molecular basis to produce compounds that are detrimental for the organoleptic quality of the wine, including some classes of volatile phenols that derive from the sequential bioconversion of specific hydroxycinnamic acids such as ferulate and p-coumarate. Although B. bruxellensis can be detected at any stage of the winemaking process, it is typically isolated at the end of the alcoh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(43 citation statements)
references
References 81 publications
1
42
0
Order By: Relevance
“…In addition, biocontrol strategies for the limitation of undesired microbial growth in foods and beverages by the application of non-Saccharomyces yeasts have been highlighted in recent years [66,67]. Berbegal et al [68] reported that the use of a mixed starter of different strains of S. cerevisiae or a mix of specific strains of non-Saccharomyces yeast with S. cerevisiae are efficient strategies in the control of the spoilage yeast like Brettanomyces bruxellensis and the volatile phenols' production in wine. Interestingly, the inoculation of different non-Saccharomyces and the inoculation time of the non-Saccharomyces yeast with respect to S. cerevisiae resources (co-inoculated and sequentially inoculated) influence the composition of the connected malolactic fermentation consortia, modulating malolactic fermentation performance [69].…”
Section: Sensory Evaluations Of Citrus Winesmentioning
confidence: 99%
“…In addition, biocontrol strategies for the limitation of undesired microbial growth in foods and beverages by the application of non-Saccharomyces yeasts have been highlighted in recent years [66,67]. Berbegal et al [68] reported that the use of a mixed starter of different strains of S. cerevisiae or a mix of specific strains of non-Saccharomyces yeast with S. cerevisiae are efficient strategies in the control of the spoilage yeast like Brettanomyces bruxellensis and the volatile phenols' production in wine. Interestingly, the inoculation of different non-Saccharomyces and the inoculation time of the non-Saccharomyces yeast with respect to S. cerevisiae resources (co-inoculated and sequentially inoculated) influence the composition of the connected malolactic fermentation consortia, modulating malolactic fermentation performance [69].…”
Section: Sensory Evaluations Of Citrus Winesmentioning
confidence: 99%
“…In the oenological environment, W. anomalus killer toxins are mainly tested against the prevailing wine spoilage microorganism Dekkera/Brettanomyces [8,65]. Nevertheless, the …”
Section: W Anomalus Produces Killer Toxins Of Broad Spectrummentioning
confidence: 99%
“…In the oenological environment, W. anomalus killer toxins are mainly tested against the prevailing wine spoilage microorganism Dekkera/Brettanomyces [8,65]. Nevertheless, the antimicrobial activity of W. anomalus towards other minor yeast species present during the early stages of grape fermentation such as P. guilliermondii or P. membranifaciens has also been reported [66,67].…”
Section: W Anomalus Produces Killer Toxins Of Broad Spectrummentioning
confidence: 99%
See 1 more Smart Citation
“…Because of this, D. bruxellensis is considered to be the only causative agent of phenolic off-odor and off-flavor production in wine fermentations [31,32]. D. bruxellensis can metabolize free-form hydroxycinnamic acids (p-coumaric acid, caffeic acid, and ferulic acid) [33]. P-coumaric acid is converted to 4-ethylphenol, a volatile phenol, and unpleasant aromas occur as the concentration of 4-ethylphenol increases [34,35].…”
Section: Wine Fermentationmentioning
confidence: 99%